Staging: Unraveling the Potassium Storage Mechanism in Graphite Foam (Adv. Energy Mater. 22/2019). Issue 22 (12th June 2019) - Liu, Jilei; Yin, Tingting; Tian, Bingbing; Zhang, Bowei; Qian, Cheng; Wang, Zhiqiang; Zhang, Lili; Liang, Pei; Chen, Zhen; Yan, Jiaxu; Fan, Xiaofeng; Lin, Jianyi; et al.
Abstract : In article number1900579, Jilei Liu, Jiaxu Yan, Xiaofeng Fan, Yizhong Huang, Ze Xiang Shen and co‐workers utilize operando techniques including Raman mapping and X‐ray diffraction (XRD), in combination with theoretical simulations, to enable the direct visualization of potassium‐intercalated graphite intercalation compounds staging evolution during electrochemical operations, with high temporal and spatial resolution. Moreover, solid evidence for a new stoichiometric formula of KC16 and an intrastage transition within stage 2 are found.